NOVUM TESTAMENTUM PATRISTICUM: Ein Projekt zur Erschließung der Rezeption des Neuen Testamentes in frühchristlicher und spätantiker Zeit - Merkt, Andreas (Sacra scripta, 2012)
The Novum Testamentum Patristicum (NTP) is a Commentary Series that evaluates the reception of the entire New Testament in ancient Christian literature and examines each passage within its respective context of reception. The first volume, Martin Meiser, Galater (NTP 9), was published in 2007 and received the “Pope Benedict XVI. Research Award”. The NTP-group is comprised of about 30 scholars from various countries, disciplines and denominations. They regularly organize international conferences on issues concerning the intersection of exegesis and patristic studies.This article demonstrates how this research initiative and especially the commentary series benefit from and complement the various instrumenta studiorum already available for those interested in the exegesis and reception of the New Testament up to the early middle ages. Scholars, also junior scholars, from Eastern European or other countries who are active in the field of patristic reception-history of the NewTestament and who are interested to participate in future conferences or eventually in the project are kindly invited to contact with the author of this article.